2021
DOI: 10.1302/2633-1462.27.bjo-2021-0058.r1
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome measures after hip fracture in patients with chronic cognitive impairment

Abstract: Aims Hip fracture patients have high morbidity and mortality. Patient-reported outcome measures (PROMs) assess the quality of care of patients with hip fracture, including those with chronic cognitive impairment (CCI). Our aim was to compare PROMs from hip fracture patients with and without CCI, using the Norwegian Hip Fracture Register (NHFR). Methods PROM questionnaires at four months (n = 34,675) and 12 months (n = 24,510) after a hip fracture reported from 2005 to 2018 were analyzed. Pre-injury score was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The study was done in two large tertiary hospitals and the results can serve as a benchmark for comparison of future PROs in patients with HF. This study had a relatively high response rate in all age groups in comparison to other HF PROs studies (15%–54%) that reported a lack of representation of older adults 61–63. It could be explained by the use of a single questionnaire that led to less survey fatigue64 and the use of sequential methods, in person and phone questioning, which has been associated with higher survey response rates 65.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The study was done in two large tertiary hospitals and the results can serve as a benchmark for comparison of future PROs in patients with HF. This study had a relatively high response rate in all age groups in comparison to other HF PROs studies (15%–54%) that reported a lack of representation of older adults 61–63. It could be explained by the use of a single questionnaire that led to less survey fatigue64 and the use of sequential methods, in person and phone questioning, which has been associated with higher survey response rates 65.…”
Section: Discussionmentioning
confidence: 76%
“…This study had a relatively high response rate in all age groups in comparison to other HF PROs studies (15%-54%) that reported a lack of representation of older adults. [61][62][63] It could be explained by the use of a single questionnaire that led to less survey fatigue 64 and the use of sequential methods, in person and phone questioning, which has been associated with higher survey response rates. 65 As opposed to other studies, 12 66 we collected patient prefracture PROs, and could evaluate the influence of the HF on the patient's outcomes, making for a more balanced comparison.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Unfortunately, dislocation of the HA lacks an ICD-10 diagnosis code, why it is difficult to find the precise number of people affected. The existing literature is unclear of the dislocation rates of the hip HA, ranging from 1 -12% (1)(2)(3)(4)(5)(6)(7)(8). Many studies describing prevalence, incidence or incidence rate base their dislocation rate on patients treated at their facility or insurance data.…”
Section: Dislocation Ratementioning
confidence: 99%
“…Knowledge of reasons for dislocation of the hip HA would help surgeons choose, or opt out, on the implant when the patient is deemed too high-risk for dislocation, or we might be able to warn the patients' of the possible risks and push them to be more careful. Thus, there are several studies suggesting some risk factors for dislocation of the hip HA, such as surgical approach (1,5,6), cognitive impairment (2,(5)(6)(7)(8), prosthesis type(4) and uncemented vs cemented implant (3). However, such studies often contradict each other, and there is a lack of conclusive evidence and the hierarchy of the proposed risk factors are unknown.…”
Section: Risk Factors For Dislocationmentioning
confidence: 99%